(untitled) (The Pakistan Development Review, 1995)
This book is an extremely valuable addition to a very important topic concerning development issues at the grassroots level. It calls attention to the difficulties related to the participatory process in the absence of effective direct communication with the ultimate beneficiaries. It is divided in four parts. The first highlights the concept underlying the use of the word "participation", a buzz-word of recent times. The authors of the different articles in this part emphasise the need to change the current patterns of development which are completely non-participatory. They relate the failures of the participatory approach to misconceiving the notion as capable of a universal application in the developed and developing countries, without due regard to the absence of some very basic prerequisites in the latter countries. In other words, the assumptions underlying the theory of the participatory approach to development in the less developed countries are found lacking due to the very different and poor economic and socio-political infrastructures in these countries. Thus, the first four chapters suggest that unless the notion of participation is systematically extended to the national and international economic and political spheres, it would fail to be of much help beyond the rural development context.